Impacts of historical ditching on peat volume and carbon in northern Minnesota USA peatlands. (15th October 2021) - Krause, Liam; McCullough, Kevin J.; Kane, Evan S.; Kolka, Randall K.; Chimner, Rodney A.; Lilleskov, Erik A.
Abstract: Peatlands play a critical role in terrestrial carbon (C) storage, containing an estimated 30% of global soil C, despite occupying only 3% of global land area. Historic management of peatlands has led to widespread degradation and loss of important ecosystem services, including C sequestration. Legacy drainage features in the peatlands of northern Minnesota, USA were studied to assess the volume of peat and the amount of C lost in the 100 years since drainage. Using high-resolution Light Detection and Ranging (LiDAR) data, we measured elevation changes adjacent to legacy ditches to model pre-ditch surface elevations, which were used to calculate peat volume loss. We established relationships between volume loss and site characteristics from existing geographic information systems datasets and used those relationships to scale volume loss to all mapped peatland ditches in northern Minnesota (USA). We estimated that 0.165 ± 0.009 km 3 of peat have been lost along almost 4000 km of peatland ditches. Peat loss upslope of ditches was significantly less than downslope ( P < 0.001). Mean width of the entire ditch-effect zone was 333 ± 8.32 m. Using our volume loss estimates, literature estimates of oxidation, and mean bulk density and peat C% values from Minnesota peatlands, we calculate a total historic loss 3.847 ± 0.364 Tg C. Assuming a constant oxidation rate during the 100 years since drainage, euic and dysic peatlands within the ditch effect zone have lost 0.26 ± 0.08 and 0.40 ± 0.13 Mg C ha −1 yr −1, respectively, comparable to IPCC estimates. Our spatially-explicit peat loss estimates could be incorporated into decision support tools to inform management decisions regarding peatland C and other ecosystem services. Graphical abstract: Image 1 Highlights: Ditch length in the peatlands of northern Minnesota was approximately 4000 km. Peat volume loss in ditches was positively related to slope degree. Volume loss was negatively related to humification and mean annual precipitation. Estimated peat loss is 165.3 ± 8.6 million m 3 peat, or 3.847 ± 0.364 Tg carbon. Our map can help guide the process of prioritization of peatland restoration.